CORAL FISH COMMUNITIES AT CORAL REEF RESTORATION SITES OF DIFFERENT AGES AT PED BEACH, NUSA PENIDA, BALI - Wilbert, Nathanael
Coral reefs are tropical coastal ecosystems that provide numerous benefits and services but are sensitive to a variety of threats, including manmade disturbances that can degrade ecosystems. Restoration and rehabilitation of coral reefs are conducted to restore and recover the complexity of the structure and function of degraded coral reef ecosystems. The most common strategy for coral reef restoration is to install artificial reef structures as substrates to support coral growth. Since 2017, several sorts of artificial reef methods have been used on Nusa Penida, Bali, particularly at Ped Beach, resulting in the formation of coral reefs of varying ages. This study aims to describe and compare reef fish communities on artificial reefs of different ages at Ped Beach, Klungkung, Nusa Penida as an indicator of the success of restoration efforts. In February 2023, data were collected at five stations: three coral reef restoration stations of varying ages (1 month, 3 years, and 6 years) and two control stations (initial habitat before restoration in the form of broken coral and soft coral and natural habitat in the form of healthy coral reefs). Coral reef cover was measured along a 10-meter line with three repetitions using the point intercept transect method. Reef fish communities were measured using the stationary point count method with a 5 meter radius and 6 repeats at each site. The percentage of coral reef cover analysis results demonstrate that the quality of coral reefs increases with age. The coral fish diversity index (CFDI) at the initial habitat and 1-month station was in the very poor category, while it was in the poor category at the 3-year and 6-year stations, where the results did not resemble fish communities on healthy (moderate) natural reefs. The richness and diversity of fish species increase from initial habitats, artificial reefs, and natural habitats. At 1 month, fish species richness was not significantly different from the baseline environment, but it was significantly different from artificial reefs at 3 and 6 years. Fish richness in the initial habitat and artificial reefs was significantly lower compared to the natural habitat. The fish diversity index did not increase significantly from the initial habitat, artificial reefs, and natural habitats. The highest fish species richness in artificial reefs was found at the 6-year station (46 ± 4.73 species) and the lowest at the 1-month station (28.8 ± 5.32 species). The highest total abundance of fish on artificial reefs was found at the 3-year station (181 ± 20.6 individuals) and the lowest at the 1-month station (78.5 ± 23.3 individuals). Visualization of fish species composition using non-metric multidimensional scaling (NMDS) showed significant differences between observation stations. Analysis of fish community composition in the functional group category revealed that the percentage abundance of carnivore functional groups associated with the initial habitat decreased not significantly with increasing age of coral reefs, whereas functional groups associated with coral reefs such as omnivores (planktivore) increased significantly. Results from this study indicate that as coral reefs age due to restoration efforts, there is an increase in the percentage of coral cover as well as the total diversity and number of fish. The composition of the fish community has likewise gradually changed.